A Singer’s Liability for the Unlicensed Use of Songs in Commercial Concerts: An Analysis of the Supreme Court’s Decision No. 825 K/Pdt.Sus-HKI/2025 - Seroja Kusuma Dewi; Rina Arum Prastyanti; Muhamad Habib (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
The Indonesian music industry keeps growing, yet compliance with royalty obligations among event organizers remains weak, shown by more than 400 events that failed to pay music royalties through the channel required by law. This problem reached its peak in the dispute between songwriter Ari Bias and singer Agnez Mo, which ended with Supreme Court Decision Number 825 K/Pdt.Sus-HKI/2025. This study aims to analyze the form of a singer's legal liability for using a song at a commercial concert without the creator's permission, and to examine whether the judges' legal reasoning aligns with the principle of copyright legal protection. This normative juridical research uses a statute approach and a case approach, examined through Hans Kelsen's Theory of Legal Responsibility and Philipus M. Hadjon's Theory of Legal Protection. The findings show that the Supreme Court corrected the singer's individual liability construction into a functional liability attached to the concert organizer. Even so, the decision only satisfies the preventive dimension of legal protection, while its repressive dimension has not yet provided real recovery for the songwriter.